2021
DOI: 10.55630/dipp.2021.11.20
|View full text |Cite
|
Sign up to set email alerts
|

A Monte Carlo Method for Image Classification Using SVM

Abstract: Support Vector Machines are a widely used tool in Machine Learning. They have some important advantages with regards to the more popular Deep Neural Networks. For the problem of image classification, multiple SVMs may be used and the issue of finding the best hyperparameters adds additional complexity and increases the overall computational time required. Our goal is to develop and study Monte Carlo algorithms that allow faster discovery of good hyperparameters and training of the SVMs, without impacting negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Earlier, Chan et al (Chan et al, 2002) reported 91% and 94% similarity success rates for second-order POLY and linear nuclei in an SVM gender classification task based on gait video sequence data. Our results also show that the SVM model can map the underlying data structures related to asymmetrical and fatigue gait (Atanassov et al, 2021). Machine learning-based classifiers can automatically recognize particular gait patterns according to their measurement methods, which is expected to provide a basis for exploring the potential biomechanical mechanism of running-fatigued.…”
Section: Discussionmentioning
confidence: 79%
“…Earlier, Chan et al (Chan et al, 2002) reported 91% and 94% similarity success rates for second-order POLY and linear nuclei in an SVM gender classification task based on gait video sequence data. Our results also show that the SVM model can map the underlying data structures related to asymmetrical and fatigue gait (Atanassov et al, 2021). Machine learning-based classifiers can automatically recognize particular gait patterns according to their measurement methods, which is expected to provide a basis for exploring the potential biomechanical mechanism of running-fatigued.…”
Section: Discussionmentioning
confidence: 79%